Pengaruh Kompetensi, Motivasi Altruistik Dan Literasi Digital Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Lingkungan Pusat Pelatihan Kelautan Dan Perikanan - Nikmatuloh, Mujib; Efendi, Suryono (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The Influence of Competence, Altruistic Motivation and Digital Literacy on Employee Performance with Job Satisfaction as an Intervening Variable in the Marine and Fisheries Training Center Environment. The method used is quantitative descriptive, Structural Equation Modeling (SEM) statistical tools. The results of this research conclude that Competence, Altruistic Motivation, Digital Literacy hAVE a positive and significant effect on job satisfaction. Competence, Altruistic Motivation, Digital Literacy hAVE a positive and significant effect on performance. Job satisfaction has a positive and insignificant effect on employee performance. Meanwhile, Job Satisfaction is not able to mediate Competence, Altruistic Motivation, Digital Literacy on Employee Performance which has an insignificant positive effect.